The Queen and Her Shrine: An Art Historical Twist on Historical Evidence Concerning the Hungarian Queen Elizabeth, neé Kotromanić, Donor of the Saint Simeon Shrine - Munk, Ana (2004)
The text will focus on the part of the visual narrative on Saint Simeon's shrine (dated to 1377-1380) that pertains to Queen Elizabeth, Queen of Hungary, and wife of Louis of Anjou. It is argued here that Elizabeth's donation was a consequence of her clear understanding of the enormous cultural and political value of relics in the Middle Ages. Elizabeth intended to reframe the mummified body of Saint Simeon in a new, Angevin context, and in a way that seems unprecedented in the reliquary medium which usually refrains from overt historical references in favor of Biblica or hagiographical narrative content. Yet, the intended Angevin propaganda was not completely successful. The people of Zadar incribed their own narrative scrutinizing Elizabeth and the Angevin presence in Zadar.
ENG